Photospheric carbon, nitrogen, and oxygen abundances of A-type main-sequence stars*. (6th September 2018) - Takeda, Yoichi; Kawanomoto, Satoshi; Ohishi, Naoko; Kang, Dong-Il; Lee, Byeong-Cheol; Kim, Kang-Min; Han, Inwoo
Abstract: Based on the spectrum fitting method applied to C i 5380, N i 7486, and O i 6156–8 lines, we determined the abundances of C, N, and O for 100 mostly A-type main-sequence stars (late B through early F at $11000\:K\gtrsim T_{\rm eff} \gtrsim 7000\:K$ ) comprising normal stars as well as non-magnetic chemically peculiar (CP) stars in the projected rotational velocity range of 0 km s$^{-1} \lesssim v_{\rm e}\sin i \lesssim \:100\:$ km s −1, where our aim was to investigate the abundance anomalies of these elements in terms of mutual correlation, dependence upon stellar parameters, and difference between normal and CP stars. We found that CNO are generally underabundant (relative to the standard star Procyon) typically by several tenths dex to ∼1 dex for almost all stars (whether CP or normal), though those classified as peculiar (Am or HgMn) tend to show larger underabundance, especially for C in late Am stars and for N in HgMn stars of late B-type, for which the deficiency even amounts up to ∼2 dex. While the behaviors of these three elements are qualitatively similar to each other, the quantitative extent of peculiarity (or the vulnerability to the physical process causing anomaly) tends to follow the inequality relation of C > N > O. Regarding the considerable star-to-star dispersion observed at any T eff, the most important cause is presumably the difference in rotational velocity. These observational facts appear to be more or less favorably comparable with the recent theoretical calculations based on the model of atomic diffusion and envelope mixing.